Das slavische Lehngut im Albanischen Teil 1: Lehnwoerter - Ylli, Xhelal (Slavistische Beitraege, 1997)
This work is the first part of a larger study of the Slavic fiefdom in Albanian, which began in 1987 and deals only with the loanwords. First, the distribution of the individual lexemes is shown in alphabetical order, then they are differentiated according to subject groups and finally according to the age of borrowing.